2014
DOI: 10.1177/1475921714522842
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of guided wave structural health monitoring using distributed adhesively bonded piezoelectric transducers

Abstract: Industrial interest in structural health monitoring of safety-critical assets is increasing. Guided wave structural health monitoring shows potential for practical use as it allows detection of small defects (1.5% reflection changes) in the presence of environmental changes. Guided wave structural health monitoring systems use bonded piezoelectric sensors to monitor wave propagation patterns and subtraction between signals and baselines from the ''healthy'' structure for robust discrimination of damage. Long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…4, 5, 6, we overlapped the experimental time of flight with the dispersion curves formulated analytically [6]. [60,61]. The agreement between the experimental results and the theoretical dispersion curves is excellent.…”
Section: Pristine Plate: Pulse-echo and Pitch-catch Measurementsupporting
confidence: 54%
“…4, 5, 6, we overlapped the experimental time of flight with the dispersion curves formulated analytically [6]. [60,61]. The agreement between the experimental results and the theoretical dispersion curves is excellent.…”
Section: Pristine Plate: Pulse-echo and Pitch-catch Measurementsupporting
confidence: 54%
“…It was demonstrated that a simple subtraction of the actual and reference signals, i.e. the residual signal, can provide the required information needed for the damage detection and its evaluation [30], [31]. However, changing environmental and operational conditions [32], [33], such as temperature and stress, can mask the signal alterations caused by the damage [34].…”
Section: Structural Health Monitoring Using Guided Wavesmentioning
confidence: 99%
“…Several promising systems have been demonstrated under laboratory conditions [3,4,5,6,7,8]. Researchers have investigated the effects of temperate [9,10,11,12,13], humidity [14] and vibration loading [15] on damage detection systems. The main focus of these works has been to assess environmental influences on pristine and damage propagation features.…”
Section: Introductionmentioning
confidence: 99%